SOI FinFET based instrumentation amplifier for biomedical applications. (September 2019) - Sonkusare, Reena; Joshi, Omkar; Rathod, S.S.
Abstract: In this paper, we present a design of SOI FinFET device based Instrumentation Amplifier (IN-Amp) for biomedical applications. An IN-Amp is operated in weak inversion regime effectively for low power and low voltage applications. The performance metrics of the proposed IN-Amp such as DC gain, Common mode rejection ratio (CMRR) were enhanced by using nanometre FinFET device technology. To achieve these desirable performance metrics, size of transistors is optimized and passive resistances are replaced by active 30 nm SOI FinFET transistor. A FinFET based DC offset removal circuit is designed to reduce the offset voltage at the output of the IN-Amp. The output achieved on appending DC offset removal circuit is exact replica of input over wide range of frequency, which can be adjusted by varying clock inputs to the circuit. It is observed that the proposed SOI FinFET based Instrumentation amplifier achieves an overall gain and CMRR of 99.6 dB and 103 dB respectively.